Nilai-nilai Pendidikan dalam Novel Eliana Karya Tere Liye - Yenhariza, Devi; Nurizzati, Nurizzati; Ratna, Ellya (Universitas Negeri Padang, 2012)
This study is purposed to describe educational values included in Eliana, the novel, which are character, intelligence, social and family prosperity educations. This study is qualitative with descriptive method, and content analysis technique. Data in the analysis is novelâ€™s elements that contain educational values. Data source is Eliana, the novel, written by Tere-Liye. This novel is published by Republika, first edition on January 2011 in Jakarta. Data collected gradually: first, read Eliana, the novel, written by Tere-Liye; second, remark sections that explain educational values; third, note data that related to educational values; and fourth, inventorying data in form.Â Based on results of Eliana, the novel, structure, these show that: (1) 19 behaviors of an actor contain character education, such as delivering order or message, honest, patient, modest, brave, sincere, and grateful; (2) 8 behaviors of an actor contain intelligence education, such as logical and creative thinking; (3) 7 behaviors of an actor contain social education, such as friendly, helping each other, respect and appreciate; and (4) 16 behaviors of an actor contain family prosperity education, such as children upbringing and household implementation.